2015
DOI: 10.1155/2015/741487
|View full text |Cite
|
Sign up to set email alerts
|

Ex VivoNicotine Stimulation Augments the Efficacy of Human Peripheral Blood Mononuclear Cell-Derived Dendritic Cell Vaccination via Activating Akt-S6 Pathway

Abstract: Our previous studies showed that α7 nicotinic acetylcholine receptor (nAchR) agonist nicotine has stimulatory effects on murine bone marrow-derived semimature DCs, but the effect of nicotine on peripheral blood mononuclear cell- (PBMC-) derived human semimature dendritic cells (hu-imDCs) is still to be clarified. In the present study, hu-imDCs (cultured 4 days) were conferred with  ex vivo lower dose nicotine stimulation and the effect of nicotine on surface molecules expression, the ability of cross-presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Our previous studies showed that nicotine treatment promotes semi-mature DCs cross-priming [711]. The mechanism of antigen uptake determined the entrance of antigens into a specific intracellular pathway, which is required for efficient cross-presentation [24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that nicotine treatment promotes semi-mature DCs cross-priming [711]. The mechanism of antigen uptake determined the entrance of antigens into a specific intracellular pathway, which is required for efficient cross-presentation [24].…”
Section: Resultsmentioning
confidence: 99%
“…MR internalized OVA target into early-endosomes, inhibit endosomes’ mature into lysosomes [15]. The treatment with nicotine not only induced the activation of Erk and p38 (Supplementary Figure S1) but also promoted the phosphorylation of PI3K and increased co-stimulatory molecules expression [1011]. Interestingly, the downstream kinases of PI3K, such as Akt, mTOR and p70S6, were efficiently activated with nicotine (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations